1998
DOI: 10.1148/radiology.207.2.9577507
|View full text |Cite
|
Sign up to set email alerts
|

Steady-state and dynamic MR angiography with MS-325: initial experience in humans.

Abstract: MS-325 provides excellent vascular and selective arterial enhancement during dynamic MR angiography. The long blood residence time also allows acquisition of steady-state images of the arteries and veins with excellent spatial resolution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
137
0
5

Year Published

1999
1999
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 230 publications
(144 citation statements)
references
References 0 publications
0
137
0
5
Order By: Relevance
“…Correlations between these parameters and histological measurements of neovasculature and macrophage content ranged from 0.74 to 0.80. Future developments in DCE-MRI of atherosclerosis may benefit from the development of new gadolinium agents with higher molecular weights to inhibit diffusion and of agents that bind to blood products such as albumin and thus remain within the blood pool (69)(70)(71). The slower kinetics of these agents may allow higher resolution imaging, where spatially resolved enhancement can be observed, for example within the fibrous cap.…”
Section: Contrast Enhancementmentioning
confidence: 99%
“…Correlations between these parameters and histological measurements of neovasculature and macrophage content ranged from 0.74 to 0.80. Future developments in DCE-MRI of atherosclerosis may benefit from the development of new gadolinium agents with higher molecular weights to inhibit diffusion and of agents that bind to blood products such as albumin and thus remain within the blood pool (69)(70)(71). The slower kinetics of these agents may allow higher resolution imaging, where spatially resolved enhancement can be observed, for example within the fibrous cap.…”
Section: Contrast Enhancementmentioning
confidence: 99%
“…16 Recently, testing has begun in humans of intravascular MR contrast agents that are retained within blood vessels and that selectively enhance the blood pool on T1-weighted MR images. [17][18][19][20][21] AMI-227 (Advanced Magnetics), an ultrasmall iron particle, has been shown to enhance vessels within the abdomen and chest in the steady state. 17,18 Another iron particle, NC100150 (Nycomed-Amersham), has recently entered human trials.…”
Section: Mra: Technical Considerationsmentioning
confidence: 99%
“…However, additional study is indicated before MRA can be relied on for evaluation of the mesenteric circulation. Recent improvements in scanner speed that allow contrast-enhanced aortography to be performed in Ïœ30 seconds, or within a breath-hold interval, 13,68 -70 and new blood-pool contrast agents currently under investigation 21 may allow additional improvements in this area.…”
Section: Mra Of the Thoracic And Abdominal Aortamentioning
confidence: 99%
“…The binding to human serum albumin reduces the extravasation of the contrast agent out of the vascular system and also leads to a high increase in relaxivity. Due to these properties MS-325 provides strong, persistent enhancement of blood vessel images (Lauffer et al 1996;Grist et al 1998). Other attempts to design blood pool contrast agents include synthesis of macromolecular gadolinium(III) chelates such as dendrimers, linear polymers, or proteins, which stay confined into blood vessels because of their large size.…”
Section: Introductionmentioning
confidence: 99%